Body mass index interacts with sex to predict readmission in in‐patients with alcohol use disorder. (2nd November 2022) - Hoffmann, Sabine; Gerhardt, Sarah; Koopmann, Anne; Bach, Patrick; Sommer, Wolfgang H.; Kiefer, Falk; Mazza, Massimiliano; Lenz, Bernd
Abstract: A previous highly controlled pilot study revealed that body mass index (BMI) predicts outcome of in‐patients with alcohol use disorder (AUD) in a sex‐specific manner. We here provide translational evidence from a daily clinical routine setting and investigated whether BMI and sex interact to predict 24‐month readmission risk in four naturalistic cohorts of a specialized addiction clinic (i.e., all patients admitted to the clinic from 2016 to 2020): (i) in‐patients (443 males and 197 females) and (ii) day clinic patients (241 males and 103 females) with a primary diagnosis of AUD; (iii) in‐patients (175 males and 98 females) and (iv) day clinic patients (174 males and 64 females) with a primary substance use disorder (SUD) other than alcohol. In the in‐patients with AUD, BMI interacted with sex to predict the 24‐month readmission risks ( p  = 0.008; after adjustment for age and liver enzyme activities: p  = 0.012); with higher BMI, the risk increases significantly in males, whereas for females, the risk tends to decrease. In the group of overweight in‐patients, we found higher readmission rates in males relative to females with an odds ratio of 1.8 ( p  = 0.038). No such significant effects were found in the other cohorts. This study's findings support previous results, suggesting that the easily accessible BMI may serve as a predictive and sex‐sensitive biomarker for outcome in in‐patients with AUD. Future studies are necessary to elucidate the underlying aetiopathological mechanisms. Abstract : Better outcome predictors are needed to improve treatments of patients with alcohol use disorder. Here, we confirmed in a clinical care setting an interaction of body mass index and sex to predict hospital readmissions; that is, higher body mass index related to higher risk in males and tended to associate with lower risk in females. The body mass index is a promising and easily accessible biomarker that might become relevant for the goals of precision medicine.